Glycosylphosphatidylinositol (GPI)-anchored surface antigens in the allogeneic activation of T cells. - Schubert, J (1995)
GPI-linked surface molecules have recently been described as structures with an activation potential for human T lymphocytes. To study the role of these molecules in T cell activation we analysed GPI-deficient or normal T cells from patients with paroxysmal nocturnal haemoglobinuria (PNH). On activation with allogeneic Epstein-Barr virus (EBV)-transformed B cell lines GPI-deficient freshly separated T cells or continuously growing T cell lines exhibited a significantly lower proliferation or cytokine production compared with their normal counterparts. In contrast, stimulation via the T cell receptor-associated CD3 structure resulted in a comparable response. There was no difference in activation of normal T lymphocytes when GPI-deficient B cells were used as stimulators compared with normal B cells obtained from the same PNH patient. We conclude from these data that GPI deficiency in PNH leads to a functional deficiency of GPI-deficient T cells. In contrast, no difference in activation of T lymphocytes for GPI-deficient cells on the stimulator cell level was observed.